Love wins the lovers and lawyers who fought the landmark case for marriage equality - Cenziper, Debbie (New York, NY William Morrow, an imprint of HarperCollinsPublishers, 2016)
"The fascinating and very moving story of the lovers, lawyers, judges and activists behind the groundbreaking Supreme Court case that led to one of the most important, national civil rights victories in decades--the legalization of same-sex marriage. In June 2015, the Supreme Court made same-sex marriage the law in all fifty states in a decision as groundbreaking as Roe v Wade and Brown v Board of Education. Through insider accounts and access to key players, this definitive account reveals the dramatic and previously unreported events behind Obergefell v Hodges and the lives at its center. This is a story of law and love--and a promise made to a dying man who wanted to know how he would be remembered. Twenty years ago, Jim Obergefell and John Arthur fell in love in Cincinnati, Ohio, a place where gays were routinely picked up by police and fired from their jobs. In 2013, the Supreme Court ruled that the federal government had to provide married gay couples all the benefits offered to straight couples. Jim and John--who was dying from ALS--flew to Maryland, where same-sex marriage was legal. But back home, Ohio refused to recognize their union, or even list Jim's name on John's death certificate. Then they met Al Gerhardstein, a courageous attorney who had spent nearly three decades advocating for civil rights and who now saw an opening for the cause that few others had before him. This forceful and deeply affecting narrative--Part Erin Brockovich, part Milk, part Still Alice--chronicles how this grieving man and his lawyer, against overwhelming odds, introduced the most important gay rights case in U.S. history. It is an urgent and unforgettable account that will inspire readers for many years to come"--Provided by publisher.
"The inspiring true story of the lovers and lawyers behind one of the most important national civil rights victories in decades- the legalization of same-sex marriage in all fifty states"--Provided by publisher.
Indignation -- Irreconcilable differences -- The boy from Sandusky -- On the matter of family -- The chicken farmer's son -- Winning for losing -- Case 773 -- Agony of law -- "Minds have changed" -- Diagnosis -- "I do" -- Duty to defend -- Good night, Husband -- Twenty-one years from midnight -- Seventy-two hours -- "All of a sudden this family was born" -- The rehearsal -- Hearts and minds -- Being there, again -- Question two -- Obergefell v. Hodges -- State interest -- Sunlight.
Keywords: Obergefell, James -- Trials, litigation, etc; Same-sex marriage -- Law and legislation -- United States -- Cases; Gays -- United States -- Biography; Lawyers -- United States -- Biography